Atrioventricular valve closure in Fontan palliation. (22nd November 2019) - King, Gregory; Winlaw, David S; Alphonso, Nelson; Andrews, David; Finucance, Kirsten; Konstantinov, Igor E; d'Udekem, Yves
Abstract: OBJECTIVES: Atrioventricular valve regurgitation is known to adversely impact outcomes of single-ventricle palliation, and valve repair rarely provides long-lasting results. Closure of a atrioventricular valve can sometimes be performed, but the long-term outcomes of this manoeuvre are unknown. METHODS: This retrospective study was conducted using patient data extracted from an existing bi-national, population-based registry of survivors of the Fontan procedure. RESULTS: Between January 1975 and June 2018, 1574 patients survived to hospital discharge with an intact Fontan circulation. Of these patients, 128 with a common atrioventricular valve were excluded. Thirty-eight patients underwent closure of an atrioventricular valve, and complete follow-up data were available for 36 patients. Twenty-nine patients underwent closure of the tricuspid valve and 7 patients underwent closure of the mitral valve. Seventeen patients underwent valve closure prior to Fontan, 13 patients underwent valve closure concomitant with Fontan and 6 patients underwent valve closure post-Fontan. Valve closure was performed using a patch technique in 29 cases and with direct suture in 7 cases. At the most recent echocardiography, 33 patients had no regurgitation, 2 patients had recurrent mild regurgitation and 1 patient had no echocardiographic follow-up. Six patients required reintervention post-valve closure and 7 patients required permanent pacemaker insertion post-valve closure. Freedom from reintervention at 1, 5 and 18 years post-valve closure was 86% [95% confidence interval (CI) 76–98%], 83% (95% CI 72–96%) and 83% (95% CI 72–96%), respectively. CONCLUSION: Atrioventricular valve closure is an effective surgical technique in selected patients with a single ventricle providing long-lasting competency in the majority of cases.